PERBANDINGAN DOMINASI BENTUK EMOSI LELAKI DALAM NOVEL PENYEBERANG SEMPADAN DENGAN KAFKA ON THE SHORE - Mahadi, Maznida; Tengku Mohd Ali, Tengku Intan Marlina (Jurnal Pengajian Melayu (JOMAS), 2018)
Emotion is a reflexive reaction associated with the human nervous system, and a mechanism for communicating feelings. The novels “Penyeberang Sempadan” (2012) by Anuar Ridhwan, and “Kafka On The Shore” (2005) by Haruki Murakami, contain psychological elements which can answer and compare hypotheses regarding men’s emotional problems. This study is based on the emotional forms categorized by Daniel Goleman in Emotional Intelligence Theory (1995) including anger, sadness, fear, pleasure, love, surprise, hate and shame. The dominant emotional forms are conveyed through the novels’ male protagonists. The comparison of dominant emotional expressions between male protagonists is based on textual content found in both novels. The analyses are based in the conflicts and problems experienced by the male protagonists, and find dominant sad emotions in both novels. Keywords: Emotional Forms, Emotional Intelligence Theory, Daniel Goleman, Sad, Dominant Emotion.